2020
DOI: 10.1177/2325967120947078
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Performance in the Women’s National Basketball Association After Anterior Cruciate Ligament Reconstruction

Abstract: Background: The incidence of anterior cruciate ligament (ACL) injuries in Women’s National Basketball Association (WNBA) athletes continues to increase. There is a paucity of data regarding return-to-play (RTP) rates and performance after ACL reconstruction in these athletes. Purpose: To quantify RTP rates and performance after ACL reconstruction in WNBA athletes. Study Design: Cohort study; Level of evidence, 3. Methods: All ACL tears sustained in the WNBA from 1997 through 2018 were identified. Body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…et al 27 also demonstrated that NBA players had a significant drop in PER in the first season after RTP that resolved by postoperative season 2 compared with a control group. Similarly, Tramer et al 31 noted a significant decline in multiple performance statistics in WNBA players' first year after RTP that also resolved at 3 seasons postsurgery. It must be noted that the aforementioned studies used the first season after RTP after ACL reconstruction as the comparative season, while the ACL cohort in the present study entered the WNBA at a mean of 3 years after their ACL reconstruction; therefore, there were no statistics readily available immediately after surgery.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…et al 27 also demonstrated that NBA players had a significant drop in PER in the first season after RTP that resolved by postoperative season 2 compared with a control group. Similarly, Tramer et al 31 noted a significant decline in multiple performance statistics in WNBA players' first year after RTP that also resolved at 3 seasons postsurgery. It must be noted that the aforementioned studies used the first season after RTP after ACL reconstruction as the comparative season, while the ACL cohort in the present study entered the WNBA at a mean of 3 years after their ACL reconstruction; therefore, there were no statistics readily available immediately after surgery.…”
Section: Discussionmentioning
confidence: 85%
“…Namdari et al 25 retrospectively reviewed 18 WNBA athletes with ACL injury and found that 14 (77.8%) were successfully able to return to competition, and while there were slight decreases in games played and MPG after ACL reconstruction, these differences were not significant. In another study focusing on WNBA players who sustained ACL tears during their professional careers, Tramer et al 31 noted that athletes returning to competition in the first year after ACL reconstruction were at risk for decreased game utilization compared with a group of heathy controls, with ACL tear athletes participating in 7.5 fewer games per season and playing 5.1 fewer MPG.…”
Section: Discussionmentioning
confidence: 99%
“…This RTP rate of ACL tears in the WNBA is consistent with a study evaluating performance effects of ACL tears in WNBA athletes that cited an RTP rate of 69.5%. 14 Importantly, this rate appears to be lower than the RTP rate of NBA players who underwent ACL reconstruction surgery, which is 88.9%. 13 NBA players who sustained a torn meniscus missed on average between 40 and 45 days, which again is also an appreciably shorter length than the RTP length of the WNBA players with similar injuries at 231 days.…”
Section: Discussionmentioning
confidence: 88%
“…), news articles, player profiles, and game previews of starting lineups were used to identify all NBA players who underwent surgical management of AP, similar to previous literature. 18 , 19 , 20 , 21 To verify these reports, at least 2 separate online articles corroborating the injury was deemed sufficient. In addition, the date of surgery was identified, and game statistics were analyzed to confirm missing data following the surgery to confirm consistency with the news reports.…”
Section: Methodsmentioning
confidence: 99%